Gas Chromatographic Prediction of Equilibrium Phase Atrazine after Sorption onto Derived Activated Carbon - Itodo, A.U.; Abdulrahman, F.W.; Hassan, L.G.; Maigandi, S.A.; Itodo, H.U. (International Journal of Poultry Science, 2009)
Inexpensive remediation method was adopted for Atrazine adsorption by derived Poultry Droppings (PD) and Poultry Wastes (PW) activated carbon. This was proposed to improve the ecological system and add value to the Biomass. GCMS quantitation was employed to investigate the sorption efficiency of the organochlorine herbicide from aqueous phase as it was evidently experimented. Performance of acid catalyzed (PD/A) and Salt treated (PW/Z) sorbents respectively demonstrated about 91.908% and 83.624% atrazine uptake, being highest in their respective series. Both filters however shows a good competitive adsorption though slightly lower than the reference commercial M&B carbon (Comm.) estimated uptake of 23.731 out of 25.00 gdm-3 valued as 94.924% removal. The role played by type of activating agent and physicochemical parameters such as density (0.250-0.496) and high porosity (00.952-0.975) were discussed. The major results support the conclusion that Gas Chromatography as a quantitative instrument is critical for isolating and detecting single equilibrium phase analyte from a multicomponent sample especially when coupled with a mass Spectrophotometer detector and with external standards from same matrix.